The effect of metal chelators on the production of hydroxyl radicals in thylakoids - Snyrychová, Iva; Pospísil, Pavel; Naus, Jan (Photosynthesis research, 2006)
The effect of metal chelators (EDTA, DTPA and Desferal) on the metal-catalyzed decomposition of hydrogen peroxide was studied using EPR spin-trapping spectroscopy. The formation of hydroxyl radicals (OH*) in both chemical (Fenton reaction) and biological (thylakoids) systems was stimulated by EDTA. DTPA promoted the generation of OH* in the presence of strong reducing agents, whereas in their absence it acted as an antioxidant. Desferal suppressed OH* production even in the presence of reductants. In our study, we have shown that metal chelators can both stimulate and suppress the formation of OH*, depending on the experimental conditions. In illuminated thylakoids we have observed prooxidant effect of EDTA and DTPA, possibly due to their reduction by some component of the electron transport chain. According to our results, metal chelators should not be used as antioxidants without prior testing of their effect in given samples.
Keywords: Thylakoids; světlo; hrách setý; kyselina pentetová; Chelating Agents; Pisum sativum; Pentetic Acid; deferoxamin; chelátory; hydroxylový radikál; tylakoidy; Light; Edetic Acid; Deferoxamine; Hydroxyl Radical; EDTA